Optically tuned terahertz modulator based on annealed multilayer MoS2 - Cao, Y.; Gan, S.; Geng, Z.; Liu, Jian; Yang, Y.; Bao, Q.; Chen, H. (Nature Publishing Group, 2016)
Controlling the propagation properties of terahertz waves is very important in terahertz technologies applied in high-speed communication. Therefore a new-type optically tuned terahertz modulator based on multilayer-MoS 2 and silicon is experimentally demonstrated. The terahertz transmission could be significantly modulated by changing the power of the pumping laser. With an annealing treatment as a p-doping method, MoS 2 on silicon demonstrates a triple enhancement of terahertz modulation depth compared with the bare silicon. This MoS 2 -based device even exhibited much higher modulation efficiency than the graphene-based device. We also analyzed the mechanism of the modulation enhancement originated from annealed MoS 2, and found that it is different from that of graphene-based device. The unique optical modulating properties of the device exhibit tremendous promise for applications in terahertz switch.